ANTHELMINTIC RESISTANCE STATUS IN STRONGYLES OF MADRAS RED SHEEP IN AN ORGANIZED FARM - M.K. Vijayasarathi; C. Sreekumar; R. Venkataramanan; M. Raman (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was carried out to detect the status of anthelmintic resistance in strongyle helminths of Madras Red sheep in an organized farm. By using faecal egg count reduction test (FECRT), coproculture, larval paralysis assay (LPA) and allele specific PCR (AS-PCR). FECR values for December 2013 and March 2014 revealed that resistance to fenbendazole (60.96 and 76.96 per cent), susceptibility to tetramisole (98.58 and 98.41per cent) and ivermectin (99.87 and 99.30 per cent). Coproculture indicated that anthelminthic resistance was established among Haemonchus contortus populations. The LD50 values for levamisole (0.0156µg/ml) obtained larval paralysis assay provided further evidence for the susceptibility to tetramisole. AS-PCR revealed the predominance of heterozygous susceptible genotype (rS) frequency from both pre and post-treatment samples. This study distinctly indicated that use of benzimidazole should be discontinued to prevent fixing of resistance.